A Clinical Analysis of Pharyngeal Bronchogenic Cysts in the Pharynx of Children - Xu, Ying; Han, Fugen; Seng, Dongjie; Jiang, Lan; Wang, Shengcai; Ni, Xin; Zhang, Jie (Frontiers in Pediatrics, 2021)
Objective: This study was designed to summarize the clinical characteristics, diagnosis and treatment of pharyngeal bronchogenic cysts in children to help in making the correct diagnosis and developing an appropriate treatment plan. Methods: The clinical data of 13 children with bronchogenic cysts in the pharynx, who were treated in otolaryngology head and neck surgery department between September 2013 and July 2019, were analyzed retrospectively. The clinical characteristics were evaluated, and the related factors for diagnosis and treatment were analyzed. Clinical characteristics and imaging features of three cases whose lesions located in the nasopharyngeal, oropharynx, and laryngopharyngeal were demonstrated. Results: All 13 children were male, the youngest being 4 days old, the oldest 6 years and 6 months, and the median age being 1 year and 4 months. Eight patients were diagnosed during a physical examination, and five patients visited the doctor with different degrees of upper airway obstruction. The mass was located in the nasopharynx in one patient, in the oropharynx in eight patients, and in the laryngopharynx in the other four patients. Computed tomography (CT) scanning, which is helpful for a topical diagnosis, showed a dense homogeneous mass. Electronic nasopharyngoscopy showed cystic masses of different sizes in the pharynx. All the children underwent cyst resection under general anesthesia, and the postoperative pathology result was a bronchogenic cyst. One child was lost to follow-up, but the remaining 12 children were followed up for between six months and six years, during which no recurrence of a cyst was found. Conclusion: Bronchogenic cysts are a rare cyst of the head and neck, and the most common site of the cyst is the oropharynx. The impact on airway obstruction depends on the location and size of the cyst. CT scanning is of great significance for diagnosis. Surgical treatment should be carried out as soon as possible after diagnosis, as surgery is the most effective way to treat bronchogenic cysts. Follow-ups should be carried out regularly to prevent cyst recurrence.